Pi of the Sky preparations for LSC-Virgo's electromagnetic follow-up project - Zadrozny, A.; Sokolowski, Marcin; Majcher, A.; Opiela, R.; Obara, L. (2015)
© 2015 SPIE. The presentation focuses on plans of the Pi of the Sky collaboration to participate in the future LSC-Virgo's Electromagnetic (EM) Follow-up campaigns. Pi of the Sky telescope participated in the first "EM Follow-up project", called Looc-Up1-3 2009-2010 organized by LSC-Virgo collaboration. Pi of the Sky brought to the project an instrument with the biggest field of view and with a very high time resolution. Recently Pi of the Sky has signed an Memorandum of Understanding (MOU) with LSC-Virgo for EM Follow-up observations in the Advanced Detector Era (ADE). Plans of the Pi of the Sky telescope for joint observations with advanced LIGO and Virgo detectors will be also outlined.